Optimasi Hidroksipropil Metilselulosa dan Carbopol terhadap Moisture Content dan Laju Pelepasan Patch Ibuprofen In Vitro (Optimization of Hydroxypropyl Methylcellulose and Carbopol for Moisture Content and Release Rate of Ibuprofen Patch In Vitro) - Kristine Dwi Puspitasari; Dwi Nurahmanto; Lidya Ameliana (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Ibuprofen is non steroidal antiinflammatory drug (NSAID) of the propionic acid class which is widely used for the treatment of rheumatoid arthritis. Ibuprofen patch is an effective approach evading ibuprofen's adverse effect in the GI tract and first pass effect. The function of polymer is to control the drug release from the patch. The aims of this study were to determine the effect of hydroxypropyl methylcellulose (HPMC) K4M and carbopol 934 combination on the moisture content (MC), in-vitro drug release, and to obtain the optimum formula of those polymers. Ibuprofen patch were prepared into three formulas based on simplex lattice design with the ratio of HPMC K4M : carbopol 934, that were 1 : 0, 0.5 : 0.5, and 0 : 1. Design expert software was used to obtain the optimum formula of both polymers. The results of this study showed that patch with HPMC K4M : carbopol 934 (0.5 : 0.5) gave the best MC and the in-vitro drug release. The optimum formula was HPMC K4M and carbopol 934 with the ratio of 0.5 : 0.5. Keywords: ibuprofen, patch, HPMC, carbopol